2013
DOI: 10.1371/journal.pone.0079921
|View full text |Cite
|
Sign up to set email alerts
|

Resequencing Three Candidate Genes for Major Depressive Disorder in a Dutch Cohort

Abstract: Major depressive disorder (MDD) is a psychiatric disorder, characterized by periods of low mood of more than two weeks, loss of interest in normally enjoyable activities and behavioral changes. MDD is a complex disorder and does not have a single genetic cause. In 2009 a genome wide association study (GWAS) was performed on the Dutch GAIN-MDD cohort. Many of the top signals of this GWAS mapped to a region spanning the gene PCLO, and the non-synonymous coding single nucleotide polymorphism (SNP) rs2522833 in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
(57 reference statements)
0
13
0
Order By: Relevance
“…Although the initial GWAS reported suggestive evidence for PCLO (Sullivan et al, 2009), and subsequent studies have reported an association with MDD (Hek et al, 2010, Aragam et al, 2011, Woudstra et al, 2012Verbeek et al, 2013), the association was not supported by results from subsequent GWAS studies (Lewis et al, 2010;Muglia et al, 2010;Rietschel et al, 2010;Kohli et al, 2011;Shi et al, 2011;Shyn et al, 2011;Wray et al, 2012), or from the recently published mega-analysis (Ripke et al, 2013) including 9240 MDD cases and 9519 controls. Based on these studies and our current results, the role of PCLO in MDD, if present, is unlikely to be very large.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although the initial GWAS reported suggestive evidence for PCLO (Sullivan et al, 2009), and subsequent studies have reported an association with MDD (Hek et al, 2010, Aragam et al, 2011, Woudstra et al, 2012Verbeek et al, 2013), the association was not supported by results from subsequent GWAS studies (Lewis et al, 2010;Muglia et al, 2010;Rietschel et al, 2010;Kohli et al, 2011;Shi et al, 2011;Shyn et al, 2011;Wray et al, 2012), or from the recently published mega-analysis (Ripke et al, 2013) including 9240 MDD cases and 9519 controls. Based on these studies and our current results, the role of PCLO in MDD, if present, is unlikely to be very large.…”
Section: Discussionmentioning
confidence: 96%
“…The third most significant single nucleotide polymorphism (SNP, rs2522833) coded for a non-synonymous amino acid change (p.Ser4814Ala) in the C2A domain of Piccolo. The association with MDD was independently reproduced by others (Hek et al, 2010;Aragam et al, 2011;Woudstra et al, 2012Woudstra et al, , 2013Verbeek et al, 2013), although it was not replicated in the more recent and largest GWAS to date (Ripke et al, 2013). A recent replicate case-control study (Minelli et al, 2012) investigated depression-related personality traits in healthy subjects as a function of the PCLO rs2522833 genotype.…”
Section: Introductionmentioning
confidence: 95%
“…Thus, it is hypothesized that dysfunction of ionotropic and metabotropic receptors are associated with the depressed phenotype. However, in a resequencing study, none of the GRM7 variants had shown the significance level with MDD in the Dutch cohort [118].…”
Section: Discussionmentioning
confidence: 99%
“…Other methods to validate or refine the identified candidate genes in future studies can be done directly by a re-sequencing approach. The advent of next-generation sequencing (NGS), and the highly decreased whole-genome sequencing associated costs, allow us to sequence specific genome regions (related to genes of interest) of a few contrasting individuals and to access, for example, by alignment algorithms, causal polymorphisms underlying these regions[ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%